Onset of depressive symptomatology in a sample of university students - Omar Enzo Santangelo; Sandro Provenzano; Dario Piazza; Alberto Firenze (Mental Illness)
The aim of the study was to evaluate depressive symptomatology within the student population of the University of Palermo (Italy). An anonymous online questionnaire was provided to the students of the University of Palermo. The first section investigated demographic and social data, while in the second section the QIDSSR16 (Quick Inventory of Depressive Symptomatology Self-Report) test was administered. 539 students (68.3% female) gave informed consent and completed the questionnaire. Considering as a dependent variable: Depressive symptomatology moderate- severe-very severe, the statistically significant independent variables associated are I don’t live with my family (aOR 1.63, 95% CI 1.01-2.63, P=0.043), I currently smoke (aOR 1.55, 95% CI 1.01-2.39, P=0.048) and Low perceived health status (aOR 4.14, 95% CI 2.73-6.28, P<0.001). Smoking is associated with an increased risk of developing a high-grade depressive symptomatology. Family plays a crucial role in decreasing the risk of moderate, severe or very severe symptoms.